Tinjauan Hukum Ekonomi Syariah Terhadap Skema Syariah Dalam Transaksi Jual Beli Rumah - Jamaludin, Mohammad (Muhammadiyah University of Surabaya, 2023)
In recent years, many home buying and selling businesses have emerged that carry the sharia system (scheme) in various cities in Indonesia. This research was conducted to answer questions about how the concept of sharia schemes is in the sale and purchase transactions of houses at the Developer Property Syariah Palangka Raya and how is the review of sharia economic law against the concept of sharia schemes in the sale and purchase transactions of these houses. This study uses a qualitative descriptive method with an economic law approach.The results of this study indicate that the concept of sharia schemes in house buying and selling transactions is carried out by eliminating banks (third parties), eliminating confiscations, eliminating insurance, Bank Indonesia (BI) checking, eliminating fines, and eliminating problematic contract. Viewed from the perspective of sharia economic law, the concept of sharia schemes in house buying and selling transactions has fulfilled the pillars and conditions of sale and purchase, however there is one condition related to the object of sale and purchase that needs to be perfected, namely related to the ownership status of the land being traded.